Rethinking Academic Integrity - Tucak, Ivana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Scientific journals represent the most important tool of communication between scientists. The key factor for the evaluation of scientists is their scientific productivity. In order for their scientific work to be positively evaluated, it is necessary for scientists to publish a considerable number of papers in journals indexed in relevant commercial databases (of which the most important are the Web of Science Core Collection and Scopus). What also matters is that the published articles are highly cited. This preoccupation with numbers has changed the publishing culture and today, scientists are more preoccupied with how much and where they publish than with what they publish. The result is a significant increase in the number of journals and published papers, but this increase does not necessarily lead to the growth of science itself. Publishing pressure is often cited as a reason for scientific misconduct. This paper explores some of the biggest challenges in academia today: transparency and impartiality of the peer review process, publication of papers in predatory journals, growth of co-authorship, prolific authors, ghost writers and honorary writers. The paper will explore these challenges in the context of the Croatian Scientific Activity and Higher Education Act and the Ordinance on Academic Promotion and Advancement Requirements and Proceedings.